PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PENEMUAN TERBIMBING PADA MATERI BANGUN RUANG SISI LENGKUNG SISWA KELAS IX DI SMPN 31 KAB. TEBO - Duwi Riskawati; Buyung Buyung; Ayu Yarmayani (Universitas Batanghari Jambi, 2018)
Abstract: This thesis was a research and development (R&D). This research aimed to produce products in the form of Mathematics Student Worksheet based on the guided discovery on the space curved side building seen from the criteria, practicality, effectiveness and validity. This research referred to the model of ADDIE development which includes five stages: analysis, design, development, implementation and evaluation. The subject of this research was the students of class IX SMP N 31 Kab. Tebo. The instruments used in this research were (a) validation sheet for the material expert, media expert and design expert to determine the validity of Student Worksheet, (b) questionnaire of student response to determine the practicality of the Student Worksheet and (c) pre-test and post-test function to determine the effectiveness of Student Worksheet.The results of the research showed that the Student-Based Student Worksheet were guided in the space curved side building of the Class XI students belonging to the good category seen from the validation of the expert who got the average score of 4.2, belonging to the practical category seen from the questionnaire of the response of the students who obtained the average score of 4.4 and classified as effectively seen from the results of the calculation of the difference between pre-test and post-test with the value of t arithmetic was 15.4 and the value of t table was 2.03. In this case, t arithmetic> t table then Ho received.Keywords: Development, Student Worksheet, Guided Discovery.